Distribution and prevalence of Nosema apis and N. ceranae in temperate and subtropical eco-regions of Argentina - Pacini, Adriana Cecilia; Mira, Anabela; Molineri, Ana Ines; Giacobino, Agostina; Bulacio Cagnolo, Natalia Veronica; Aignasse, Andrea María Elisa; Zago, Luis Fernando Basili; Izaguirre, Mercedes; Merke, Julieta; Orellano, Emanuel; Bertozzi, Ezequiel; Pietronave, Hernan Pablo; et al. (2017)
A total of 361 colonies from 59 apiaries located in two temperate and three subtropical eco-regions were examined during the post-harvest period to determine distribution and prevalence of Nosema spp. Apiaries from subtropical eco-regions showed a lower spore count than those from temperate ecoregions. Pure N. ceranae and co-infection were detected in apiaries from all regions. In contrast, pure N. apis infection was exclusively observed in the subtropical study region. The predominant detection of N. apis in a subtropical region joining a southern temperate region where mainly co-infected apiaries were identified is in contrast to previous reports.